1989
DOI: 10.1111/j.1749-6632.1989.tb22505.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies of the Interaction of Heparin, Low Molecular Weight Heparin and Heparinoids with Platelets

Abstract: Heparin, low molecular weight heparins, and heparinoids were studied for their ability to inhibit the aggregation of platelets by various agonists and for their ability to adhere to collagen. Heparin was a very effective inhibitor of aggregation with collagen and with ristocetin as it was with adhesion to collagen. The heparinoids showed little effect on aggregation or adhesion. Heparan sulfate and pentosan polysulfate did show slight inhibitory activity against collagen aggregation and adhesion and both inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 41 publications
1
21
0
1
Order By: Relevance
“…Since there was no change in the platelet count, hematocrit or fibrinogen content, it appears that heparin inhibited platelet adhesion to the collagen membrane and platelet thrombus formation. Some re ports have indicated that heparin inhibits both von Willebrand factor-platelet binding and von Willebrand factor-dependent platelet function [10,24]. Using a hemostatometer, which can detect platelet reactivity to shear stress by measuring the blood perfusion pres sure through a polyethylene tube with holes, John et al [11,12] demonstrated that heparin inhibited the platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there was no change in the platelet count, hematocrit or fibrinogen content, it appears that heparin inhibited platelet adhesion to the collagen membrane and platelet thrombus formation. Some re ports have indicated that heparin inhibits both von Willebrand factor-platelet binding and von Willebrand factor-dependent platelet function [10,24]. Using a hemostatometer, which can detect platelet reactivity to shear stress by measuring the blood perfusion pres sure through a polyethylene tube with holes, John et al [11,12] demonstrated that heparin inhibited the platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this is thought to be that APC binds to membrane phospholipids and exerts its anticoagulant activity only in the solid phase where a clot is formed [9], whereas heparin binds with antithrombin III and exerts its anticoagulant effect in the fluid phase. Furthermore, Mcssmorc et al [10] and John et al [11,12] indicated that heparin inhibited platelet function, and this may be another mechanism by which hemorrhage de velops. In this regard, the interaction of APC with platelets is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the same range of concentrations, heparin and low molecular weight heparins inhibited platelet aggregation (21). Preliminary results obtained either by means of aggregation tests or ELISA detection of antibodies bound to multimolecular PF4-heparin complex indicated that SR 90107A/Org 3 1540 did not crossreact in v i m with antibodies present in the plasma of patients with heparin associated thrombocytopenia (13,21, Amiral et al, submitted).…”
Section: Effect On Plateletsmentioning
confidence: 99%
“…[16] In vitro and in vivo, fondaparinux approved for the prevention of VTE recurrence, [52] a study evaluathad no direct effect on Factor IIa. [39] It also does not bind significantly to platelet factor 4 in manufacturer's prescribing information, [11,54] and drug interaction plasma from patients with heparin-induced thrombocytopenia studies in healthy volunteers. [39] It also does not bind significantly to platelet factor 4 in manufacturer's prescribing information, [11,54] and drug interaction plasma from patients with heparin-induced thrombocytopenia studies in healthy volunteers.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%